Perbedaan Return Saham Pada Monday Effect di Bursa Efek Indonesia (Studi Pada Emiten Yang Masuk Dalam Perhitungan JII Selama Desember 2013 - Mei 2014) - Nugraha, Wildan Aditya; Herlambang, Leo (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
Monday effect is an information used by investors to adjudge their investment decision inÂ accordance with some conditions. The condition is able to make changes into stock supplyÂ and demand. The change of stock supply and demand generate fluctuating stock return.Â The purpose of this research is to analyze the reaction of sharia capital market over theÂ Monday effect depicted by the difference of stock return before and after Monday.This research uses event study approach, applied to JII listed issuers in December 2013 âÂ May 2014. The 5-days observation period was used in this research which is consist of t-2 (2Â days before Monday), t-0 (event date), t+2 (2 days after Monday). The hypothesis test wasÂ ran through paired sample t-test.In accordance with the statistic test result using significant rate (Î±) 5%, the probability ofÂ this research was 0,001 depicting the difference of stock return before and after Monday.